2017
DOI: 10.1016/j.jpsychores.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Fear and distress disorders as predictors of heart disease: A temporal perspective

Abstract: Objective Few studies have been able to contrast associations of anxiety and depression with heart disease. These disorders can be grouped in fear and distress disorders. Aim of this study was to study the association between fear and distress disorders with subsequent heart disease, taking into account the temporal order of disorders. Methods Twenty household surveys were conducted in 18 countries (n=53791; person years=2,212,430). The Composite International Diagnostic Interview assessed lifetime prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…For example, fear weakens the immune system, and is associated with cardiovascular diseases, fatigue, long-term memory impairment, mood swings, among others (Robinson et al, 2013;208 Margarida Jarego et al anales de psicología / annals of psychology, 2023, vol. 39, nº 2 (may) Roest et al, 2017;Rosenberg, 2017;Segerstrom & Miller, 2004). In recent studies about the effects of COVID-19related fear, fear of COVID-19 was found to be associated with an increase in reported depression, anxiety, stress, social isolation, loneliness, sleep problems, and cognitive functioning impairment (Baker et al, 2016;Bitan et al, 2020;Bjursell, 2020;Fofana et al, 2020;Koçak et al, 2021;Pyszczynski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fear weakens the immune system, and is associated with cardiovascular diseases, fatigue, long-term memory impairment, mood swings, among others (Robinson et al, 2013;208 Margarida Jarego et al anales de psicología / annals of psychology, 2023, vol. 39, nº 2 (may) Roest et al, 2017;Rosenberg, 2017;Segerstrom & Miller, 2004). In recent studies about the effects of COVID-19related fear, fear of COVID-19 was found to be associated with an increase in reported depression, anxiety, stress, social isolation, loneliness, sleep problems, and cognitive functioning impairment (Baker et al, 2016;Bitan et al, 2020;Bjursell, 2020;Fofana et al, 2020;Koçak et al, 2021;Pyszczynski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that prevalence of anxiety in heart failure patients ranged 11% to 70% in different to the literatures [ 3 8 ]. Severe anxiety is also associated with the incident cardiovascular diseases [ 9 , 10 ] and also with increased mortality risk of heart failure patients particularly when LVEF is severely decreased [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7] Further, it has been found that poor healthcare seeking behaviour was associated with the fear of being diagnosed of heart diseases and other NCDs. [8] Recently an investigation found a good proportion of men who were scared of being diagnosed of infertility, and accepting vasectomy as a family planning method which as such, prevented them from willingly seeking healthcare. [9] The fear of HIV/AIDS is not different which still lingers till today where people hardly give themselves for voluntary testing to know their status.…”
Section: Introductionmentioning
confidence: 99%